Perlindungan Hak Cipta Seni Batik Jambi Kreasi Modifikasi Di Kota Jambi - Syarifa Mahila; Tresya Tresya (Universitas Batanghari Jambi, 2020)
Traditional Batik Art has been modified by batik artisans, which in the Copyright Act is referred to as contemporary batik art (see article 40 letter J). Modified Batik Art has received protection through the Copyright Act, but not all people understand it. For this reason, it is necessary to study and examine how the legal culture of the community is towards an applicable regulation. This research is an empirical legal research conducted in Jambi City by using an interview method by purposive sampling of respondents who understand the object of study under study. Batik craftsmen in the city of Jambi also develop traditional batik by doing imagination based on their own creativity or also based on the tastes of consumers, but they still consider it not so important as the meaning of registration. The batik craftsmen prioritize maintaining the quality of their work. Some have registered their work as a patent because they consider it more appropriate to register it as a patent related to the process of making batik with priority to quality, which of course requires a separate method